The female religious mobilization linked to the court of Isabel La Católica: Doña María Dávila and her foundations - Graña Cid, María del Mar (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The interesting phenomenon of spiritual promotion by some ladies of the court of Queen Isabel the Catholic is yet to study in its implications. These pages are devoted to the study of one of them, Doña María Dávila, Virreina Of Sicily, focusing the analysis in her foundational work of religious and charitable institutions, as well as in the devotions that she spread through it. they raise the need to relate the context, religious pre-reform, with the contemporary debate known as «Querelle des femmes». this leads to a political intent in the defense of the female sex, the memory of the queens rulers and the interest by claiming the compatibility between femininity and the exercise of power.